PENGARUH KARAKTERISTIK PERUSAHAN TERHADAP PENGUNGKAPAN ASET BIOLOGIS PADA PERUSAHAAN SEKTOR AGRIKULTUR PERIODE 2019-2023 - Tarigan, Naufal Detra Utoyo; Sirait, Devi Ayu Putri; Rana Fathinah Ananda; Warsani Purnama Sari; Sucitra Dewi (Program Studi Akuntansi Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The purpose of this study is to examine the effects of company size, public ownership, and biological asset intensity on the degree of biological asset disclosure in agricultural firms that are listed between 2019 and 2023 on the Indonesia Stock Exchange. Even after PSAK 69 was put into effect, there were still differences in disclosure levels across corporations, which prompted this inquiry. It's crucial to remember that prior research on this topic has frequently produced contradictory or conflicting results. The study uses a quantitative technique and purposive selection to choose 13 organizations as samples in order to accomplish these goals. To analyze the data, multiple linear regression was used. The findings show that biological asset disclosure is significantly improved by business size. However, there was no discernible impact from either biological asset intensity or public ownership alone. Curiously, the degree of sharing was significantly impacted by all three criteria at the same time. From a theoretical standpoint, this research enhances the use of stakeholder and agency theory in the agriculture industry. Practically speaking, these results may help investors make informed decisions about their investments and motivate businesses to increase the openness of their reporting.